A Novel HCC Prognosis Predictor EEF1E1 Is Related to Immune Infiltration and May Be Involved in EEF1E1/ATM/p53 Signaling - Han, Ruiqin; Feng, Penghui; Pang, Junyi; Zou, Dingfeng; Li, Xiaolu; Geng, Chao; Li, Lili; Min, Jie; Shi, Jing (Frontiers in Oncology, 2021)
Background EEF1E1 has been reported to play a role in ovarian cancer, breast cancer, non-small cell lung cancer and other cancers, but its role and mechanism in hepatocellular carcinoma (HCC) are still unknown. Methods EEF1E1 expression in human HCC was analyzed via the GTEx and TCGA database. Logistic regression analysis was used to analyze the clinicopathological correlation of EEF1E1 expression. The correlation between EEF1E1 expression and patients’ prognosis was analyzed in HCC, shown by forest plots, nomogram and Kaplan–Meier curves. Hazard ratio (HR) with 95% confidence intervals and log-rank p-value were calculated via multivariate/univariate survival analyses. Moreover, the correlation between EEF1E1 and tumor immune infiltration was analyzed using the gsva package with the ssgsea algorithm. Pearson correlation was used to investigate the correlation between EEF1E1 expression and p53 pathway genes expression. Two third-party databases were used to validate the content of EEF1E1 protein and mRNA expression patterns and prognosis analysis. The immunohistochemistry and multiplex immunohistochemistry was used to verify the bio-informatics results. Results EEF1E1 mRNA and protein expression in tumor was statistically higher than normal (EEF1E1 mRNA: p < 0.001; EEF1E1 protein: p < 0.01). Results from paired t-test (cancer and adjacent tissues) exhibited consistent trend (t = 7.572, p < 0.001). Immunohistochemistry showed that EEF1E1 is highly expressed in cancer. The expression of EEF1E1 was positively correlated with body weight, BMI, tumor status, vascular invasion, AFP, logistic grade, T stage and pathological stage. The univariate Cox model revealed that high EEF1E1 expression was strongly associated with worse OS (HR=2.581; 95% CI: 1.782-3.739; p < 0.001), as was T stage, pathologic stage, Histologic grade. High EEF1E1 expression was the only independent prognostic factor associated with OS (HR=2.57; 95% CI: 1.715-3.851; p < 0.001) in the multivariate analysis. EEF1E1 was significantly correlated with various immune cells, including cytotoxic cells, DC, macrophages, neutrophils, NK cd56bright, TFH, Tgd, Th17, Th2, Treg. Multiplex immunohistochemistry showed that the EEF1E1 protein level is positively correlated to the CD3, CD4, PD1 and is negatively correlated to the CD8. The expression level of EEF1E1 in HCC was significantly correlated with the key genes involved in the p53 pathway. The expression of EEF1E1, ATM, p53 and CASPASE3 in HCC tissues was significantly higher than that in adjacent tissues. Conclusion EEF1E1 is highly expressed in cancer tissues in HCC. EEF1E1’s high expression is significantly correlated with worse prognosis and immune cell infiltration of HCC. EEF1E1 may be participating in EEF1E1/ATM/p53 signaling pathway in HCC.